Effects of body weight on the clinical and radiological outcomes of children with flexible flatfeet managed with the 'calcaneo-stop' procedure. Issue 3 (May 2019) - Pavone, Vito; Vescio, Andrea; Canavese, Federico; Costa, Danilo; Sessa, Giuseppe; Testa, Gianluca
Abstract : This study aimed to evaluate the clinical and radiological outcomes of normal, overweight, and obese children with symptomatic flexible flatfeet managed with the 'calcaneo-stop' procedure (CSP), and to determine whether any correlation exists between patient weight and outcome. One hundred and seventy-four symptomatic flexible flatfeet were managed with CSP during the study period. The patients were divided into three groups according to their BMI and weight Z -scores: normal, overweight, and obese. Their clinical and radiographic outcomes were assessed preoperatively, and at 1 and 5 years after the index procedure. Although the radiographic criteria were comparable between the three groups, the clinical outcome was worse in obese children than in normal and overweight patients ( P <0.05). BMI and the Z -score affected the outcomes of obese patients treated with CSP for symptomatic flexible flatfeet. Although the radiographic outcome was similar irrespective of BMI and Z -scores, obese patients had significantly lower clinical scores than the other patients.